Fa’ āliyyatu Istikhdām Kitāb Al I’rōb Fi qowā’idi Al Lughah Al ‘Arobiyyah Litarqiyyati Mahāroh Al Qirō’ah Litthullābi Al Faslu Al Tsālis Al Ibtidā’i - Baharun, Segaf; Al-Farizi, Abdul Qowi; Arisandi, Yusuf (Al-Jadwa: Jurnal Studi Islam, 2024)
Good reading results from understanding speech or paying attention to something heard, which is a condition for protecting a person from many mistakes. This study aims to determine how to teach reading skills using Arabic grammar parsing books to third-year construction students at the Dar es Salaam Institute, Malang and the effectiveness of using Arabic grammar parsing books to improve the reading skills of third-year elementary school students at the Dar es Salaam Institute, Malang. The method of this experimental research is using pre- and post-tests for the control group and the experimental group. The approach used is the quantitative approach. The tools for collecting data in this research are: observation, interview, and test. The results of the research indicate the T score calculated in this research (3.54) is greater than the T score in the table at the 5% level (2.06) and the T score in the table at the 1% level (2.80). We know that the previous hypothesis is acceptable, and this indicates that using the book on parsing Arabic grammar in teaching the Arabic language to teach reading skills is effective. 2) Using the book on parsing in Arabic grammar makes students feel enthusiastic and easy to improve their reading skill and find ease in determining the parsing in sentences. In conclusion, the use of the Arabic grammar parsing book in teaching the Arabic language to teach reading skills to third-year primary school students at the Dar es Salaam Malang Institute is effective in the effectiveness and development of students’ desire and motivation to improve reading skills.